Approaches for the Development of Rapid Serological Assays for Surveillance and Diagnosis of Infections Caused by Zoonotic Flaviviruses of the Japanese Encephalitis Virus Serocomplex. (18th April 2012) - Hobson-Peters, Jody
Abstract : Flaviviruses are responsible for a number of important mosquito-borne diseases of man and animals globally. The short vireamic period in infected hosts means that serological assays are often the diagnostic method of choice. This paper will focus on the traditional methods to diagnose flaviviral infections as well as describing the modern rapid platforms and approaches for diagnostic antigen preparation.